2022
DOI: 10.1177/00076503221114795
|View full text |Cite
|
Sign up to set email alerts
|

From the Substantive to the Ceremonial: Exploring Interrelations Between Recognition and Aspirational CSR Talk

Abstract: Stakeholder recognition constitutes a firm’s experience of affirmation and acknowledgment from stakeholders and is deemed essential for organizations to develop positive self-relations and a sense of themselves as morally responsible social actors. Through an in-depth case study, I show how a firm’s varied experiences of stakeholder recognition for its corporate social responsibility (CSR) efforts alternately facilitated and hindered the performativity of its aspirational CSR talk through two key processes: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 55 publications
(121 reference statements)
0
19
0
Order By: Relevance
“…The link between the prevailing understanding of CSR, and its potential as an access good, also provides further insights into the performativity of CSR (Christensen et al, 2013; Crane and Glozer, 2016; Schoeneborn et al, 2020; Trittin‐Ulbrich, 2022) beyond the firm‐level. The discursive co‐construction of CSR ideas and aspirations not only creates new framings of CSR issues (see Gond and Nyberg, 2017, p. 1136 on ‘ontological effects’), but also directly affects the processes of corporate access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The link between the prevailing understanding of CSR, and its potential as an access good, also provides further insights into the performativity of CSR (Christensen et al, 2013; Crane and Glozer, 2016; Schoeneborn et al, 2020; Trittin‐Ulbrich, 2022) beyond the firm‐level. The discursive co‐construction of CSR ideas and aspirations not only creates new framings of CSR issues (see Gond and Nyberg, 2017, p. 1136 on ‘ontological effects’), but also directly affects the processes of corporate access.…”
Section: Discussionmentioning
confidence: 99%
“…The discursive co‐construction of CSR ideas and aspirations not only creates new framings of CSR issues (see Gond and Nyberg, 2017, p. 1136 on ‘ontological effects’), but also directly affects the processes of corporate access. The public nature of these CSR talks (Christensen et al, 2013, p. 382) and their recognition by other stakeholders (Trittin‐Ulbrich, 2022) within political arenas makes these CSR ideas more formative and binding. Since access is a precondition for lobbying influence (Bouwen, 2002; Werner, 2012), this may ultimately influence the types of policy to be adopted and how they promote specific types of corporate behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As organizational research has also suggested, distally framed actions cause these actions to be downgraded in importance and to be viewed as less urgent, therefore allowing the response to be delayed (Gan et al, 2015; Nadkarni et al, 2019; Shu & Gneezy, 2010). Using a future temporal focus to talk about meta social themes that do not fully reflect already existing practices may also have a self-persuasive effect because it raises expectations and scrutiny, and could mobilize expectations of better practices (Christensen et al, 2020; Schoeneborn et al, 2020; Trittin-Ulbrich, 2023). In other words, the use of the future tense shows commitment to such pressing issues while deferring their solution to the future.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Second, the extant formative literature mainly focuses on the boundary conditions under which CSR talk gains performativity and enhances a firm's commitment to substantive CSR efforts such as stakeholder recognition (Trittin-Ulbrich, 2023) or even to external stakeholders' negative evaluations (Haack et al, 2021). The role of companies' home-country cultural characteristics has, however, been neglected.…”
mentioning
confidence: 99%